2020
DOI: 10.1002/mbo3.998
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia–host cell contact controls the transcription activity of the trimeric autotransporter adhesin BCAM2418 gene

Abstract: Cell‐to‐cell early contact between pathogens and their host cells is required for the establishment of many infections. Among various surface factors produced by bacteria that allow an organism to become established in a host, the class of adhesins is a primary determinant. Burkholderia cenocepacia adheres to the respiratory epithelium of cystic fibrosis patients and causes chronic inflammation and disease. Cell‐to‐cell contacts are promoted by various kinds of adhesins, including trimeric autotransporter adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…B. cenocepacia TAAs have been studied in detail during the past years, and are known to be multifunctional proteins involved in many virulence related traits like biofilm formation, motility, adhesion and invasion of host cells 9 , 11 , 13 , 66 , 67 . The expression of BCAM2418 and BCAS0236 TAA encoding genes during the early stages of B. cenocepacia infection was demonstrated in a recent work 12 . The overexpression of BCAM2418 transcripts shown to be variable over time, reaching a maximum after 30 min of B. cenocepacia adhesion to bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…B. cenocepacia TAAs have been studied in detail during the past years, and are known to be multifunctional proteins involved in many virulence related traits like biofilm formation, motility, adhesion and invasion of host cells 9 , 11 , 13 , 66 , 67 . The expression of BCAM2418 and BCAS0236 TAA encoding genes during the early stages of B. cenocepacia infection was demonstrated in a recent work 12 . The overexpression of BCAM2418 transcripts shown to be variable over time, reaching a maximum after 30 min of B. cenocepacia adhesion to bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…The overexpression of BCAM2418 transcripts shown www.nature.com/scientificreports/ to be variable over time, reaching a maximum after 30 min of B. cenocepacia adhesion to bronchial epithelial cells. Also, the bacterial interaction with specific host-cell receptors, namely O-linked glycosylated proteins, was reported to be the trigger for the increased expression of BCAM2418 TAA 12 . The obtained data in this work seems to support those observations as BCAM2418 TAA expression increased after bacterial interaction with the host-cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient binding of laminin via multiple bacteria receptors was found crucial for H. influenzae pathogenesis [3 ▪ ]. In many Gram-negative bacteria trimeric autotransporter adhesins enable bacterial adhesion to extracellular matrix, also to epithelial cells, and were recently investigated for A. baumannii (Ata protein), Brucella spp., B. cenocepacia , and H. influenzae (Hia proteins) [6 ▪ ,7 ▪ ,8]. They are in the focus of recent research since, besides adhesion and invasion, they are immunogenic and thus, currently reviewed as potential vaccine candidates [31].…”
Section: Adhesion and Invasion As Critical Steps To Cause Intracellul...mentioning
confidence: 99%
“…Intracellular persistence during an infection displays an important strategy of bacterial pathogens to hide from antibiotics and the immune system. Such bacteria found strategies to adhere to and to invade the potential host [3 ▪ ,4,5 ▪ –7 ▪ ,8], survive host-defense mechanism such as oxidative stress and phagolysosomal fusion and adapt to the intracellular environment [9 ▪ ,10,11 ▪ ]. Indeed, some bacteria found mechanisms to dormantly persist for long-term [12] or to escape the host by apoptosis induction allowing further bacterial spreading [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that B. cepacia causes many clinical problems by attaching to biotic and abiotic surfaces. 6,7 It can be found in humid areas in the hospital such as food, sinks, toilets, floor cleaning cloths, respiratory equipment, dialysis equipment, plastic tubing of catheters, and even disinfectant solutions. 8 The experimental work on the adhesion of B. cepacia to the plastic tubing of indwelling urinary catheters (IDCs) is not clearly described in the literature.…”
Section: Introductionmentioning
confidence: 99%